SHIFTING STRATEGY FOR ENDEK BALI WEAVING MSMES TO SURVIVE IN THE COVID-19 PANDEMIC - I Kadek Pande Sutanegara (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Digital strategies that must be carried out in the new normal era by MSME owners to maintain the economic stability of a business they have, change the way of working from a different perspective with the aim of keeping the organization going during the Covid-19 Pandemic. The digitalization strategy provides views for MSME owners to make decisions in determining the right company's vision and mission in dealing with this Pandemic. Qualitative research with case studies on nine MSMEs in Klungkung Regency, researchers conducted direct interviews in terms of MSME productivity and their new way of working. The results of this study produce a scientific model that describes the state of MSMEs during a pandemic where most of the employees have been laid off, and productivity has drastically decreased. The role of the Government is also very important to support MSMEs in product marketing to support the Bali economy and with the support of MSMEs by the Bali Provincial Government, MSME owners must certainly be able to take advantage of the situation to find ways to survive and rise from this situation by using SWOT Analysis. Product development in innovation of new ideas, such as selling cloth masks with Endek motifs and also marketing carried out using digital media such as sales through e-commerce and social media such as existing marketplace platforms and business actors are required to be able to adapt to changing market situations in order to produce products. modern and latest in accordance with the trends in the market so that it will be in demand by everyone.